Pencegahan dan Pengendalian Diabetes Melitus Melalui Pilihan Nutrisi dan Diet Pada Ibu-Ibu PKK Desa Batan, Banyudono, Boyolali - Haryoto; Fadhilah, Arini; Fauzi, Ahmad (Abdi Geomedisains, 2025)
Diabetes mellitus (DM) is a chronic metabolic disease with an increasing prevalence due to unhealthy lifestyles and limited public knowledge, including among PKK women in Batan Village, most of whom do not yet understand how to choose healthy foods to prevent and manage DM. This community service program aimed to improve the understanding of PKK members in Batan Village, Banyudono, Boyolali, regarding DM management through proper nutrition and dietary education. The activities were carried out in three stages: fasting blood glucose screening, nutrition counseling, and interactive discussions. Among the 21 participants, 42.86% showed fasting blood glucose levels exceeding 110 mg/dL. The educational materials emphasized the selection of foods with a low glycemic index and the avoidance of foods high in added sugars. The discussion sessions revealed that most participants initially lacked understanding of DM prevention; however, after the program, around 85% of participants were able to mention foods recommended for DM patients and understood the concept of portion control. The education was also contextualized by promoting local food ingredients such as sweet potatoes and peanuts. This program demonstrated that a community-based educational approach can be an effective non-pharmacological strategy to reduce the risk of DM and improve community quality of life, as evidenced by the increase in participants’ understanding, with 85% able to mention recommended foods for DM patients and understand portion control concepts after the education. Simple direct educational interventions proved successful in building significant preventive health awareness.